Promoting sustainable green roofs through Leadership in Energy and Environmental Design (LEED) - Hake, Aubrey (Kansas State University, 2007)
The multidisciplinary quality of green roofs involves landscape architects, architects, structural engineers, horticulturalists, and increasingly ecologists in design and implementation. A standard of measurement of green roof sustainability is necessary with increasing professional and public interest in green roofs and green roof impact on stormwater and urban ecology. Currently, green roof LEED (Leadership in Energy and Environmental Design) credits do not address the sustainability of green roofs. The intent of this research is to take a critical look at green roof sustainability in regards to the United States Green Building Council (USGBC) LEED green building standard credits. It is also my intent to be (at least) a small, yet integral part in advancing the LEED standards and environmental standards as a whole. Precedent studies, archival research and professional interviews provide a solid foundation for the development of green roof LEED credits to measure success and increase green roof sustainability. Dialog with the USGBC and professionals provide a sound base for the development of the green roof criteria.
Keywords: Green roofs; Leadership in energy and environmental design; LEED; Landscape Architecture (0390)